Developing and Sustaining Positive Relationships through Stakeholder Engagement - Christopher Jochum; Paul Adams; Shawn Henderson (Academic Chairpersons Conference Proceedings, 2018)
Developing and sustaining positive working relationships with stakeholders is an increasingly important component of departmental leadership. Participants in this session will learn how a teacher education department successfully engages stakeholders to promote student success, encourage fund raising initiatives and support the university and departmental culture.
Keywords: Stakeholders; leadership; student success; fund raising; university culture